2001
DOI: 10.1248/bpb.24.1258
|View full text |Cite
|
Sign up to set email alerts
|

Expression Profiling of Sulfotransferases in Human Cell Lines Derived from Extra-Hepatic Tissues.

Abstract: Cytosolic sulfotransferases (SULTs) are phase II drug-metabolizing enzymes that catalyze the transfer of a sulfonate group from 3Ј-phosphoadenosine 5Ј-phosphosulfate (PAPS) to molecules possessing phenols, enols, alcohols or amines. Sulfo-conjugation confers greater polarity and water solubility on the parent molecules, thereby facilitating biliary or urinary excretion and detoxification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 26 publications
1
28
0
Order By: Relevance
“…It also should be noted that, whereas glucuronidation of the unmethylated flavonoids in general predominated in the liver, sulfation was more important in the Caco-2 cells. This is consistent with previous observations and is dependent on tissue-specific expression of these enzymes (Glatt, 2000;Tamura et al, 2001).…”
Section: Discussionsupporting
confidence: 94%
“…It also should be noted that, whereas glucuronidation of the unmethylated flavonoids in general predominated in the liver, sulfation was more important in the Caco-2 cells. This is consistent with previous observations and is dependent on tissue-specific expression of these enzymes (Glatt, 2000;Tamura et al, 2001).…”
Section: Discussionsupporting
confidence: 94%
“…After incubations of hesperetin with Caco-2 cell monolayers, formation of hesperetin 7-O-glucuronide and 7-O-sulfate was observed, whereas no metabolites of hesperetin conjugated at position 3Ј were detected. These observations could be explained by the relatively strong expression of SULT1C4 (Tamura et al, 2001;Meinl et al, 2008b) and UGT1A6 (Paine and Fisher, 2000), both enzymes specifically catalyzing the conjugation at position 7, compared with other SULT or UGT forms in Caco-2 cells. Moreover, small interfering RNA-mediated UGT1A6 silencing in this cell line heavily decreased the glucuronidation of the flavonoid apigenin, which demonstrates an important role for UGT1A6 in the glucuronidation by Caco-2 cells of a structurally related compound .…”
Section: Discussionmentioning
confidence: 99%
“…at ASPET Journals on May 10, 2018 dmd.aspetjournals.org published by Tamura et al (2001) on the expression of various SULT mRNA in Caco-2 cells. These findings will be discussed under Discussion.…”
Section: Sulfotransferase Expression In Caco-2 Cellsmentioning
confidence: 99%
“…Despite its origin from a tumor, the Caco-2 cell line has retained the ability to differentiate into polarized epithelial monolayers and shows numerous biochemical and morphological characteristics of enterocytes (e.g., formation of microvilli, tight junctions and desmosomes, and expression of brush-border enzymes such as sucrase-isomaltase) (Hidalgo et al, 1989). Caco-2 cells express various phase 1 and phase 2 enzymes, e.g., CYP1A1 (Boulenc et al, 1992) and CYP1B1 (Buesen et al, 2002;Lampen et al, 2004) and sulfotransferases 1A1 and 1A3 (Tamura et al, 2001), as well as transport proteins of the ATP-binding cassette family, such as P-glycoprotein (Hunter et al, 1993;Hirohashi et al, 2000), multidrug resistance-associated proteins, and breast cancer resistance protein (Taipalensuu et al, 2001). However, levels of transporters (Lennernas et al, 1996) and xenobiotic-metabolizing enzymes (Caro et al, 1995) may substantially vary from those found in intestine.…”
mentioning
confidence: 99%